Numerical modelling of onshore wind turbine gravity foundations susceptible to cyclic soil degradation - Seymour, Steven (Department of Civil Engineering, 2019)
South Africa is currently one of the global leaders in emerging wind markets. This development has come about since the country adopted a new approach towards sustainable growth and development. However, wind turbine structures present unconventional and complex design challenges, largely because they are subject to highly fluctuating and irregular cyclic loads. Accordingly, one of the major uncertainties in the design of wind turbines is accurate prediction of the long-term performance of the foundation. In this regard, a particular issue relates to founding conditions comprised of softer or plastic soil layers, where the effects of cyclic degradation need to be taken into consideration during the design stage. Cyclic degradation refers to the phenomenon in which the stiffness of soil decreases progressively when subjected to cyclic loading. This reduction in soil stiffness occurs due to deterioration of the soil microstructure, as well as accumulation of excess pore water pressure, with the extent of it being largely dependent on the shear strain level in the soil and the number of loading cycles. Accounting for the potential reduction in soil stiffness is crucial when dimensioning the foundation of a wind turbine, as wind turbines are dynamically sensitive structures, with their natural frequencies being dependent, inter alia, on the stiffness of the underlying soil. However, despite the possible implications of cyclic degradation, there is a present lack of guidance provided in design guidelines to explicitly incorporate it into design. The primary objective of this study was to investigate the effect of cyclic soil degradation on the design of onshore wind turbine gravity foundations. This was undertaken by: (1) analysing a case study of a wind farm in South Africa, and quantifying the effect of cyclic degradation on the foundation design for three separate ground profiles; (2) performing a parametric study to identify key parameters controlling cyclic degradation in the context of wind turbine foundations. Numerical modelling was undertaken to investigate these objectives, through the development of three-dimensional finite element models in the software package RS3 by Rocscience. The three ground profiles analysed were selected from the wind farm based on the presence of soils that were deemed susceptible to cyclic degradation, as well as to illustrate different scenarios in ground conditions. Using these ground profiles, it was demonstrated how appropriate ground moduli could be selected for design, such that they were representative of the time-related cyclic degradation. This was achieved by assessing the depth of influence of cyclic degradation in the numerical models, and applying a reduction factor to the soil stiffness within this depth in the evaluation of the minimum required foundation diameter. Several parameters were varied in the parametric study. Regarding soil properties, the plasticity index, initial shear modulus G0, and degradation shear strain threshold γtv were identified as having a significant effect in governing the extent of cyclic degradation. Furthermore, it was observed that altering the foundation diameter also had a considerable impact on the depth of influence of cyclic degradation, particularly for very soft profiles. Finally, an assessment of different load cases indicated that cyclic degradation may not only occur in rare conditions, but is also likely to accumulate in normal operating conditions during the lifetime of the structure. This emphasised the importance of accounting for cyclic degradation in design.